Research Progress of TXNIP as a Tumor Suppressor Gene Participating in the Metabolic Reprogramming and Oxidative Stress of Cancer Cells in Various Cancers - Chen, Yiting; Ning, Jieling; Cao, Wenjie; Wang, Shuanglian; Du, Tao; Jiang, Jiahui; Feng, Xueping; Zhang, Bin (Frontiers in Oncology, 2020)
Thioredoxin-interacting protein (TXNIP) is a thioredoxin-binding protein that can mediate oxidative stress, inhibit cell proliferation, and induce apoptosis by inhibiting the function of the thioredoxin system. TXNIP is important because of its wide range of functions in cardiovascular diseases, neurodegenerative diseases, cancer, diabetes, and other diseases. Increasing evidence has shown that TXNIP expression is low in tumors and that it may act as a tumor suppressor in various cancer types such as hepatocarcinoma, breast cancer, and lung cancer. TXNIP is known to inhibit the proliferation of breast cancer cells by affecting metabolic reprogramming and can affect the invasion and migration of breast cancer cells through the TXNIP-HIF1α-TWIST signaling axis. TXNIP can also prevent the occurrence of bladder cancer by inhibiting the activation of ERK, which inhibits apoptosis in bladder cancer cells. In this review, we find that TXNIP can be regulated by binding to transcription factors or other binding proteins and can also be downregulated by epigenetic changes or miRNA. In addition, we also summarize emerging insights on TXNIP expression and its functional role in different kinds of cancers, as well as clarify its participation in metabolic reprogramming and oxidative stress in cancer cells, wherein it acts as a putative tumor suppressor gene to inhibit the proliferation, invasion, and migration of different tumor cells as well as promote apoptosis in these cells. TXNIP may therefore be of basic and clinical significance for finding novel molecular targets that can facilitate the diagnosis and treatment of malignant tumors.